Asincronie e peculiarità della comunicazione in Italia - Solito, Laura; Sorrentino, Carlo (SocietàMutamentoPolitica, 2011)
The media have become increasingly autonomous frm the politics and they are expanding social space. The increase of the social actors who have access to the media triggered the overcoming of information monopolies and allowed the entry of citizens in many areas of public discourse. The authors analyze the meanings and consequences of changes in the media system in Italy, still characterized by an asymmetry of the communication flows.